(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The prognosis of colorectal carcinoma is poor despite the availability of multidisciplinary approaches. The histological type, grade, and stage are the classical prognostic parameters for colorectal cancer. Still, treatment response differs within the same grade or stage due to the molecular heterogeneity of the tumors. CDX2 is a marker unique to the intestinal epithelial cells and acts as a tumor suppressor in colorectal cancer. CDX2 expression decreases in high-grade and advanced stages of CRCs, negatively affecting the patient’s prognosis. This study was intended to evaluate the expression pattern of CDX2 in colorectal adenocarcinoma and assess its association with prognostic parameters. Materials and methods: This cross-sectional observational study was done in the Department of Pathology of Chittagong Medical College in Chattogram, Bangladesh spanning from March 2019 to February 2021. Surgically resected specimens from forty-five patients with colorectal adenocarcinoma were included. CDX2 protein expression was analyzed immunohistochemically. Results: CDX2 high expression was seen in 42.2% of cases and low in 57.8%. The proportion of low expression of CDX2 was significantly higher among the patients with a higher tumor grade (P=0.021). There was no statistically significant association between CDX2 expression and other prognostic variables. Conclusion: In this study, high-grade colorectal adenocarcinoma cases displayed diminished or absent CDX2 expression. Its expression pattern may be helpful in predicting the clinical outcome of the patients and also directing appropriate treatment strategies. JCMCTA 2024 ; 35 (1) : 58-65